2005
DOI: 10.1542/peds.2004-2022
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the Mass Media, Body Shape Concerns, and Use of Supplements to Improve Weight and Shape Among Male and Female Adolescents

Abstract: ABSTRACT. Objective. To assess the prevalence and correlates of products used to improve weight and shape among male and female adolescents.Methods. A cross-sectional study was conducted of 6212 girls and 4237 boys who were 12 to 18 years of age and enrolled in the ongoing Growing Up Today Study. The outcome measure was at least weekly use of any of the following products to improve appearance, muscle mass, or strength: protein powder or shakes, creatine, amino acids/hydroxy methylbutyrate (HMB), dehydroepiand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
2
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(129 citation statements)
references
References 20 publications
7
113
2
7
Order By: Relevance
“…Four large national surveys have assessed the lifetime prevalence of AAS use in American teenage girls (CDC, 2003(CDC, ,2005Field et al, 2005;SAMHSA, 1994) -yielding grossly discrepant estimates, ranging from 0.1% to 7.3% (Table 1). These discrepancies cannot reasonably be attributed to sampling differences, because the surveys showed no comparable differences in their prevalence estimates for other drugs, such as cannabis ( Table 1).…”
Section: National Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Four large national surveys have assessed the lifetime prevalence of AAS use in American teenage girls (CDC, 2003(CDC, ,2005Field et al, 2005;SAMHSA, 1994) -yielding grossly discrepant estimates, ranging from 0.1% to 7.3% (Table 1). These discrepancies cannot reasonably be attributed to sampling differences, because the surveys showed no comparable differences in their prevalence estimates for other drugs, such as cannabis ( Table 1).…”
Section: National Studiesmentioning
confidence: 99%
“…The Growing up Today study-Unlike the CDC and MTF studies, the Growing up Today (GUT) study (Field et al, 2005) places its "steroid" question last in a series of seven questions regarding substances typically used for muscle gains, fat loss, or athletic performance ( Figure 1). Therefore, having just answered the six previous questions, respondents are well cued that "anabolic/injectable steroids" refers to AAS as opposed to, say, corticosteroids.…”
Section: Thementioning
confidence: 99%
“…When comparing our results to the findings of a recent study conducted in United Arab Emirates, the internet was the most influential method on body image 47.3 and 42 % of boys and girls, respectively, followed by television (31 % boys and 37 % girls) [34]. The impact of the media on body weight perceptions among adolescents has been examined by numerous studies from western countries [12,[35][36][37]. Achtenberg [36] reported that magazine and printed media had very strong and consequential effect on body image among American adolescent girls [36].…”
Section: Discussionmentioning
confidence: 59%
“…Achtenberg [36] reported that magazine and printed media had very strong and consequential effect on body image among American adolescent girls [36]. Findings from a survey of adolescent girls conducted in the United States showed that 69 % of the participants reported that images of girls displayed in magazines influence their concerns of the perfect body shape and 47 % reported that the images forced them to lose weight [37]. Some researchers illustrated that girls who read fashion magazines often compared themselves with the models that appear in the television advertisements and the magazine articles, resulting in more negative feelings about their own body figure [12,35,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation